Impact of an inquiry-oriented proposal for promoting technology-enhanced learning in a post-pandemic context - Campillo-Ferrer, José-María; Miralles-Martínez, Pedro (Frontiers in Education, 2023)
This study examines the effectiveness of learning processes developed through a technology-enhanced approach in higher education. Therefore, we analysed Webquests together with other gamification resources, considered relevant research studies on the impact and advantages of this inquiry-oriented learning approach, and examined students’ perceptions of the effects of these online learning tools on developing their organisational skills and effective planning for learning. Participants in the study were 73 student teachers enrolled in the core unit of Social Studies, in the second year of the Primary Education degree at the University of Murcia (Spain). In this study, a pre-test and posttest design was applied and questionnaires were administered to students at the beginning and end of the term to examine the impact of this inquiry-oriented approach on the development of students' learning processes. Their perceptions of the learning achieved were analysed using statistical software for Excel (XLSTAT). The results indicate that these online tools effectively promote technology-enhanced learning and collaborative work, especially among the most motivated and digitally literate students, underlining the importance of motivation and digital literacy as catalysts for learning. The study also highlights the need for further research on the impact of digital resources in promoting competency-based learning alongside other motivational online approaches in tertiary education.